Implementation Social and Emotional Learning (SEL): Promoting Students’ Learning Activities - Arieny, Mutiara; Kartika, Dewi; Tibrani, Mgs. Muhammad (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
This research is motivated by issues that indicate the students' activities at Senior High School 2 Palembang in biology education are still below the minimum criteria. The purpose of this study is to promoting students' learning activities in the topic of ecosystems by implemented of Social Emotional Learning (SEL). Method of this research is Classroom Action Research (CAR) design involving planning, action, observation, and reflection cycles during 2 cycles. In this research, the sample consists of students from class X.7. The data collected included observations of students' learning activities and documentation. The observation of learning activities covers several aspects, including visual activities, oral activities, writing activities, and mental activities. The results showed a significant increase in the percentage of students' average learning activity scores, from 37.1875% before the implementation (Pre-cycle) of Social Emotional Learning to 53.90625% after the implementation of Cycle I of Social Emotional Learning, and further increased to 77.5% after the implementation of Cycle II of Social Emotional Learning. Based on the results, it can be concluded that the implementation of Social Emotional Learning has significant potential in improving students' learning activities in the ecosystem subject.